Mechanical compressor-driven thermochemical storage for cooling applications in tropical insular regions. Concept and efficiency analysis. (1st June 2018) - Ferrucci, Franco; Stitou, Driss; Ortega, Pascal; Lucas, Franck
Highlights: Combination of a thermochemical reactor and a mechanical vapor compression unit. The system can provide cooling and energy storage in the context of smart microgrids. Thermochemical method presents no self-discharge and long charge/discharge life cycle. The compressor aids the desorption and compensates for a low heat source temperature. With a waste heat source it attains a cooling capacity of 4 kWhcold /day/m 2 of PV panel. Abstract: The energy situation in tropical insular regions, as is found in French Polynesia, presents a number of challenges, including heavy dependence on imported fuel, high transport costs from the mainland and weak electricity grids. By contrast, these regions possess a variety of renewable energy resources, which are favorable for the exploitation of smart micro grids and energy storage technologies. With regards to electrical energy demand, the high temperatures commonly seen in these regions throughout the entire year implies that a large proportion of electricity consumption (∼40%) is used for space cooling, even during evening hours. Framed within this context, this paper presents an air conditioning system driven by photovoltaic electricity that combines a mechanical vapor refrigeration system and a thermochemical storage unit. Thermochemical processes enable the storage of energy in the form of chemical potential with virtually no losses, which can be used to produce cold during the evening hours without running a compressor. These processes are implemented using thermochemical reactors, in which a reversible chemical reaction between a solid compound and a gas takes place. The solid/gas pair used in this study is barium chloride salt (BaCl2 ) reacting with ammonia (NH3 ), which is also the coolant fluid in the refrigeration circuit. In the proposed system, the photovoltaic-driven electric compressor is used during the day either to run the refrigeration circuit when a cooling demand occurs or to decompose the ammonia-charged salt and to remove the gas from the thermochemical reactor when there is no cooling requirement. During the evening, when there is no electricity from solar sources, the system changes its configuration and the reactor reabsorbs the ammonia gas from the evaporator to produce cold. The efficiency of this hybrid system is evaluated in this work and compared with alternative processes which utilize either electrochemical (lead-acid, lithium-ion batteries) or thermal storage (ice, chilled water) for cold production.